2015
DOI: 10.1016/j.tjog.2014.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chemerin rs17173608 polymorphism on polycystic ovary syndrome susceptibility

Abstract: These results suggested that there was a significant association between chemerin rs17173608 polymorphism and the PCOS; but this relationship was affected by obesity status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Studies have reported the pleiotropic effects of RARRES2 SNPs, including a varying adiposity status, visceral fat mass, metabolic syndrome, and polycystic ovary syndrome [ 24 26 , 50 , 51 ]. The SNP rs17173608, the most commonly reported SNP associated with all the aforementioned phenotypes in non-Asian populations, was not associated with chemerin levels or various clinical characteristics, inflammatory biomarkers, or adipokines in our study population.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported the pleiotropic effects of RARRES2 SNPs, including a varying adiposity status, visceral fat mass, metabolic syndrome, and polycystic ovary syndrome [ 24 26 , 50 , 51 ]. The SNP rs17173608, the most commonly reported SNP associated with all the aforementioned phenotypes in non-Asian populations, was not associated with chemerin levels or various clinical characteristics, inflammatory biomarkers, or adipokines in our study population.…”
Section: Discussionmentioning
confidence: 99%
“…There have been reports of higher serum levels of chemerin among women with PCOS and obese females 107 . In Iran, a significant association was found between the chemerin rs17173608 polymorphism and PCOS 108 …”
Section: Inflammationmentioning
confidence: 96%
“…107 In Iran, a significant association was found between the chemerin rs17173608 polymorphism and PCOS. 108…”
Section: Chemerinmentioning
confidence: 99%
“…Increased serum chemerin in women with PCOS, with or without obesity, suggest that chemerin may be involved in the development of the pathogenesis of PCOS [132]. It has also been shown that there is no significant association between chemerin rs17173608 gene polymorphism and PCOS, after adjusting genotypes for BMI; notedly, this relationship was affected by obesity status [133]. An interesting result was published by Adrych et al According to the authors, there is an association between chronic pancreatitis in humans and an increased serum chemerin concentration [134].…”
Section: Adipokinesmentioning
confidence: 99%